(untitled) (Journal of Economic Research & Business Administration, 2016)
In any modem economy, lombard organizations play a considerable role, because they offerservices, that are alternative for bank services, and therefore increase competition at the credit market and diversification of financial instruments. The guarantor of stability to any organization is a high level of organization control system, one of basic elements of which is the properly organized internal audit. In small lombards, where sizes and scales of operations and risks not only justify the necessity of creation of the special subdivision on realization of internal audit but also separate worker on a complete rate in the state of lombard organization, all activity on an internal audit can come true by an external contractor. The attracted structures for realization of internal audit mostly are large consulting or public accountant organizations.